Permeable Conductors for Wearable and On‐Skin Electronics. Issue 1 (31st October 2021) - Chen, Fan; Huang, Qiyao; Zheng, Zijian
Abstract : The booming development of wearable and on‐skin electronics has driven increased interest in flexible and stretchable conductors, which serve as the indispensable building blocks for these electronic devices. However, conductors for such soft electronics are mostly fabricated with impermeable elastic thin films, which not only affect the long‐term wearing comfort but also limit the device's multifunctionality. In recent years, permeable conductors, conducting materials that are fabricated based on breathable materials and structures with deformability, have shown great promise for applications in wearable and skin‐mountable electronics. Herein, a specific perspective on the development of permeable conductors that can simultaneously display conductivity, flexibility or stretchability, and permeability to air, moisture, and liquid is provided. Key design considerations of permeable conductors, as well as the state‐of‐the‐art strategies to endow flexible and stretchable conductors with permeability, are discussed. Finally, key challenges and future directions of permeable conductors and electronic devices are discussed along with the analysis of possible solutions. Abstract : Herein, key design considerations for developing conductors for wearable and on‐skin electronics are discussed. The state‐of‐the‐art strategies to simultaneously enable the conductors conductive, flexible or stretchable, and permeable to air, moisture, and liquid are summarized. Challenges and prospects of permeable electronics are also discussed.